Nursing to achieve organizational performance: Consider the role of nursing intellectual capital. Issue 3 (May 2016) - Harris, Alexandra
The success and performance of healthcare organizations relies on the strategic management of knowledge. Nursing Intellectual Capital (NIC) has emerged as a concept involving nursing knowledge resources that create value in healthcare organizations. This article aims to discuss the importance of considering knowledge resources in the context of healthcare performance, with specific reference to NIC. Reflections are then provided on how leaders can look to advance NIC for improved performance.